Analysis Of Criminal And Criminal-Procedural Legislation Of Foreign Countries Regulating Proceedings Up To Trial For Crimes Of Violation Of Statute Rules Of Relationships Between Non Subordinate Military Servants - Alautdinov Dilmurad Alautdin Ogli (Zien Journals, 2023)
Through this article, you can learn about the analysis and specifics of the norms that regulate the conduct of proceedings before the court in connection with the crime of violation of the charter provisions regarding the interaction between military personnel who are not subordinate to each other in the criminal and criminal-procedural legislation of foreign countries. The analysis of the norms regulating the conduct of proceedings before the court regarding the crime of violation of the charter provisions regarding the mutual relations between military personnel who are not subordinate to each other in the criminal and criminal-procedural legislation of foreign countries is aimed at improving the criminal legislation.
Keywords: non-subordinate serviceman; statutory provisions; objective party; routine humiliation